Tax Revenue In Asian Countries: Contribution Of Economic Sector With The Rule Of Law As A Moderating Variable - Wijaya, Suparna; Putri, Yuninda Anggraini (WIM Solusi Prima, 2024)
The implementation of government effectiveness aims to provide the best service to the community. The effectiveness of this organization can be measured by one of them using The Worldwide Governance Indicators (WGI) project index. From 2010 to 2019, there are seven Asian countries with effectiveness indexes above the world average, namely Georgia, Hong Kong, Thailand, Japan, South Korea, Singapore, and Malaysia. Through this study, it will be assessed whether this effectiveness supports tax revenue by conducting research on the effect of the contribution of the industrial sector and the service sector to Gross Domestic Product (GDP) on the effect of tax revenue. Then the author also conducts research whether the interaction of moderating variables, in this case the Rule of Law Index variable with the two independent variables (the contribution of the industrial sector and the service sector to Gross Domestic Product (GDP)) has an influence on the contribution of tax revenue to GDP considering that law enforcement is one of the steps in the implementation of controlling tax payments. The results obtained in this study state that before the interaction with moderating variables, the independent variables, namely the industrial sector and the service sector in GDP contribution, have a significant negative effect on tax revenue. Then when the moderating variable, namely the rule of law index, interacts with the industrial sector and the service sector, the effect of the two independent variables on the tax revenue variable has increased to a significant positive effect, so that the moderating variable in this study has a role that strengthens the influence of the independent variable on the dependent variable.